Appendiceal agenesis discovered incidentally at laparotomy for suspected acute appendicitis: a case report and review of the literature - Khan, Muhammad Naseer; Khiyal, Maaz; Khan, Muhammad Bilawal; Tufail, Muhammad; Rehman, Abdul (Journal of the Pakistan Medical Association, 2025)
The vermiform appendix is a vestigial organ in humans. The congenital absence of the appendix was first described by Morgagni in 1719. Since then, more than a hundred such cases have been reported. The estimated incidence of this condition, based on autopsy studies and laparotomies, is 1 in 100,000, which is exceptionally rare. Nevertheless, given that acute appendicitis is one of the most common causes of abdominal pain, and is the most common indication for emergency abdominal surgery, the practising surgeon needs to be aware of this clinical entity as it can potentially lead to diagnostic confusion and even iatrogenic injuries. Hereby, we report the case of an 18-year-old girl, who presented with symptoms suggestive of acute appendicitis and was found to have congenital absence of the appendix intra-operatively. Keywords: Appendicitis, Vermiform Appendix, Congenital Abnormalities, Anatomic Variation.